Ag-Co bimetallic catalyst for electrochemical reduction of CO2 to value added products. (March 2017) - Singh, Surya; Gautam, Rajeev K.; Malik, Karan; Verma, Anil
Graphical abstract: Highlights: Bimetallic Ag-Co catalyst is evaluated for electrochemical reduction of CO2 . Ag and Co have synergetic effects on reaction product formation. CH4, C2 H4 and CO were the reaction products. Abstract: Direct electrochemical reduction of carbon dioxide to values added products is one of the most promising and challenging techniques. Moreover, the lack of availability of efficient, selective and stable electrocatalysts is a major difficulty for efficient CO2 reduction. Various materials including metals, metal oxides, and metal complexes have been studied to increase the Faradaic efficiency, selectivity, and to reduce the energy input for the generation of hydrocarbons. Herein, we report a non-noble bimetallic electrocatalysts based on Ag-Co that is hardly evaluated for the electrochemical reduction of CO2 in-spite of the proven synergetic effect of bimetals for various chemical reactions. Therefore, the present study investigates the role of bimetallic electrocatalyst for the CO2 electrochemical reduction. A bimetal electrocatalyst is synthesized by Co and Ag metals to investigate the effect of the bimetal over gas phase CO2 electrochemical reduction. It is found that though the chosen metals are individually selective for the CO formation but the combination results in CH4 and C2 H4 formation along with CO. The maximum Faradaic efficiency found for CH4 is 19.5% at 2 V using Ag-Co.